Neurogenin-2 induced neuronal differentiation in co-cultured bone marrow stromal and neonatal cortical cells - Saba Majeed; Aisha Aziz; Kanwal Iftikhar; Shabana Usman Simjee (Journal of the Pakistan Medical Association)
Objective: To explore a novel and dynamic role for neurogenin-2 in promoting cortical neurogenesis in cells produced from co-culturing neonatal cortical neural progenitor cells with bone marrow stromal cells.